Identifying Radicalism Potential in Senior High School Students in Riau Province - Zarkasih, Zarkasih; Yusro, Nelly; Vebrianto, Rian; Thahir, Musa (Islam Realitas: Journal of Islamic and Social Studies, 2022)
This study aims at identifying the radicalism potential in senior high school students or equivalent levels including secondary schools and vocational schools in Riau Province. This study uses a survey design involving 230 students selected through random sampling consisting of 65 senior high school students, 100 vocational high school students, and 65 Islamic senior high school students. The collected data were analyzed qualitatively and quantitatively. The findings showed the radicalism potential of 20% in secondary school students, of 30.5% in vocational school students, and of 19.8% in Islamic secondary school students. Around 23.4% of the students were identified to have radicalism potential such as having fundamentalist behavior. The percentage obtained in this study is hoped to encourage the teaching of religious tolerance, universal morality, and formal education. Another implication for the people who are related to the education of youth is that they should pay more attention more to difficult social issues, especially those that are relevant to the use of social media.Penelitian ini bertujuan untuk mengidentifikasi potensi radikalisme pada siswa SMA/MA di Provinsi Riau. Designm penelitian ini menggunakan survey melibatkan 230 siswa yang diambil secara random sampling yang terdiri dari 65 siswa SMA, 100 siswa SMK, dan 65 SMA Islam. Data yang terkumpul dianalisis secara kualitatif dan kuantitatif. Hasil penelitian menunjukkan potensi radikalisme pada siswa SMA 20%, siswa SMK 30,5%, dan siswa MAN Islam 19,8%. Sekitar 23,4% siswa diidentifikasi memiliki potensi radikalisme seperti berperilaku fundamentalis. Persentase yang didapat dalam penelitian ini kurang sehingga diharapkan dapat dilaksanakan pengajaran tentang pentingnya toleransi beragama, akhlak, dan pendidikan formal. Implikasi lain bagi masyarakat yang terkait denganperan pemuda harus lebih memperhatikan kisruh yang ada, terutama yang relevan dengan penggunaan media sosial di era milenial ini